Pengaruh Kecekapan Pekerja Sosial Dalam Pemulihan Dadah Terhadap Kepuasan Klien Di Balai Pemulihan Sosial Pamardi Putra, Bandung, Indonesia - Aritonang, Admiral Nelson (2013)
The handling of substance abuse is conducted by social workers in a rehabilitation institution, but the competencies of social workers in providing service to the clients are not yet optimal. This condition can be viewed by the number of clients dropping out from the institution even though the services provided by social workers have not been completed. When the clients are given an opportunity to stay a few days with their family, some used narcotics again so that when they return to the institution to participate in the advanced programme the clients need to adjust with the relapse situation. The objective of the research is first, to analyze how the level of knowledge about drugs, basic skill, the method of intervention that exist in social workers and the difference of clients’ satisfaction before and after social workers gained the training. Second, to analyze how the partial influence of knowledge about substance of social workers to the clients’ satisfaction. Third, to analyze how the partial influence of basic skills which is conducted by social workers to the clients’ satisfaction. Fourth, to analyze how the partial influence of intervention method which is conducted by social workers to the clients’ satisfaction. Fifth, to analyze how the simultaneous influence about knowledge, basic skills and intervention method which exist in social workers to the clients’ satisfaction.Sixth, to develop a social service model in the institution in order to improve clients’ satisfaction. This research used quantitative method with two research designs namely quasi experiment and explanatory research.